Comparison of the low and high/very high cycle fatigue behaviors in Ni microbeams under bending - Barrios, Alejandro; Kakandar, Ebiakpo; Castelluccio, Gustavo M.; Pierron, Olivier N. (Springer, 2021)
The present work demonstrates a micromechanical technique to investigate the low cycle fatigue (LCF) behavior of Ni microbeams under fully reversed bending loadings. The technique extends the range of measured fatigue lives from the previously reported technique for high and very high cycle fatigue (HCF/VHCF) characterization in the same microbeams. The results highlight significant differences in the slope of stress and strain-life behavior and crack propagation rates that differ from an average of 10–12 m/cycle in HCF/VHCF to an average of 10–8 m/cycle in LCF. These results, in addition to postmortem fractography work, suggest that the mechanisms follow the conventional mechanisms of crack tip stress intensification in the LCF regime. This is in stark contrast to the void-controlled mechanisms that were previously identified in the HCF/VHCF regime. These results demonstrate that the transition in governing mechanisms from void-controlled to conventional mechanisms is highly influenced by the size effects present in the microbeams.
Keywords: Fatigue; Microelectromechanical systems (MEMS); Ni; Electrodeposition; Microscale